Adding Bricks to Clicks – Online Retail Evolution - Agnes Sophie Roggentin; Ramona Waldau (Marketing Review St.Gallen, 2019)
The integration of an offline channel creates various (non-)monetary benefits for former pure online retailers. Nevertheless, this strategic development is an ongoing learning process for retailers and involves a fundamental corporate culture change. It therefore needs to be pursued cautiously, given the challenges that will arise.
Keywords: 650